Almat TYPOLOGY OF ITERATIVE CONSTRUCTIONS IN ENGLISH AND UZBEK LANGUAGES: TYPOLOGY OF ITERATIVE CONSTRUCTIONS IN ENGLISH AND UZBEK LANGUAGES - Abdullayev, Almat (Журнал иностранных языков и лингвистики, 2022)
The main aim of this introduction article is to give a general overview of how habituality has been investigated in the literature as a grammatical category. In doing so, we first elaborate on the question of how habituality can be characterized and what difficulties one encounters in determining its properties, which include non-contingent modal event recurrence. A brief discussion of these issues is given in Section . Outlines selected (conceptual and formal) connections between habituality and other grammatical categories. What our observations essentially indicate is that habituality, on the one hand, closely interacts with several TAM categories, most prominently imperfective aspect and its derivatives (progressive, continuative), and also interacts in special ways with modal categories, such as the evidential or the future, on the other hand, we also observe – as has been done previously – that habituality is often not encoded overtly and can be expressed by several forms within one and the same language, and if overtly marked by a dedicated form, diachronically, it is not always stable. Finally, summarizes the most relevant findings of the articles collected in the present special issue and highlights their importance for the general discussion about habituality.